Prebiotic Inulin and Sodium Butyrate Attenuate Obesity-Induced Intestinal Barrier Dysfunction by Induction of Antimicrobial Peptides - Beisner, Julia; Filipe Rosa, Louisa; Kaden-Volynets, Valentina; Stolzer, Iris; Günther, Claudia; Bischoff, Stephan C. (Frontiers in Immunology, 2021)
Defects in the mucosal barrier have been associated with metabolic diseases such as obesity and nonalcoholic fatty liver disease (NAFLD). Mice fed a Western-style diet (WSD) develop obesity and are characterized by a diet-induced intestinal barrier dysfunction, bacterial endotoxin translocation and subsequent liver steatosis. To examine whether inulin or sodium butyrate could improve gut barrier dysfunction, C57BL/6 mice were fed a control diet or a WSD ± fructose supplemented with either 10% inulin or 5% sodium butyrate for 12 weeks respectively. Inulin and sodium butyrate attenuated hepatosteatitis in the WSD-induced obesity mouse model by reducing weight gain, liver weight, plasma and hepatic triglyceride level. Furthermore, supplementation with inulin or sodium butyrate induced expression of Paneth cell α-defensins and matrix metalloproteinase-7 (MMP7), which was impaired by the WSD and particularly the fructose-added WSD. Effects on antimicrobial peptide function in the ileum were accompanied by induction of β-defensin-1 and tight junction genes in the colon resulting in improved intestinal permeability and endotoxemia. Organoid culture of small intestinal crypts revealed that the short chain fatty acids (SCFA) butyrate, propionate and acetate, fermentation products of inulin, induce Paneth cell α-defensin expression in vitro, and that histone deacetylation and STAT3 might play a role in butyrate-mediated induction of α-defensins. In summary, inulin and sodium butyrate attenuate diet-induced barrier dysfunction and induce expression of Paneth cell antimicrobials. The administration of prebiotic fiber or sodium butyrate could be an interesting therapeutic approach to improve diet-induced obesity.